Using your hard disk. - Ainsbury, Robert D. (Indiana : Que® Corporation, 1990)
"Using Your Hard Disk from Que is a definite must! This full-featured user's guide includes a bound-in disk packed with tools to improve your hard disk performance, Using Your Hard Disk is the essential disk-management guide for all DOS users. Informative examples and easy-to-follow tẹxt teach you how to effectively manage your hard disk with batch files, commans, and the most popular hard disk utility programs. You learn the "ins and outs'" of hard disk structure, operating systems, menu environments, file managers, and backup and recovery tools. In addition, you can find useful information at a glance with the extensive command reference and glossary. Ensure the peak performance of your personal computer with Que's valuable book-and-disk set-Using Your Hard Disk! Learn how to... • Efficiently organize files and directories • Navigate the pathways of your hard disk • Creațe powerful batch files • Avoid virus infection • Safeguard against data loss • Optimize your hard disk's performance." (Copiado de la pasta).
Introduction. Part I. Hard disk basics. Part II. Dos basics. Part III. Hard disk organization and management. Part IV. Getting the most from your hard disk. Part V. Maintaining hard disk security. Glossary of hard disk terms. Index.
Includes utilities diskette.
Keywords: COMPUTERS -- HARD DISK; ELECTRONIC DATA PROCESSING; OPERATIONAL SYSTEMS -- COMPUTERS; COMPUTER -- PROGRAMMING; DISCO DURO -- COMPUTADORA; PROCESAMIENTO ELECTRÓNICO DE DATOS; SISTEMAS OPERACIONALES -- COMPUTADORES; PROGRAMACIÓN -- COMPUTADORES